The New Growth Evidence - Temple, Jonathan (Journal of Economic Literature, 1999)
Why do growth rates differ? This paper surveys the recent empirical literature on economic growth, starting with a discussion of stylized facts, data problems, and statistical methods. Six research questions are emphasized, drawing on growth and convergence research. In answering these questions, the paper argues that efficiency has grown at different rates across countries, casting doubt on neoclassical models in which technology is a public good. The latter half of the paper rounds up a variety of findings before providing answers to all six questions, including a short summary of how differences in growth rates arise.